The moral sphere of the personality and its essential definitions - Savchyn, Myroslav (Psyhology & society, 2022)
The issue of morality in modern psychological discourse and life activity of a human, group, society in general is analyzed. The importance of its theoretical rethinking is stated, starting from the ideas of man of ancient thinkers, including Plato, where the ontological marker of a perfect society and a separate person considered authenticity, creation of good, usefulness, expediency, harmony of existence and essence. The essence of man is denied in the idea of simulacra (sophists) as a false copy in imitation, when his ability to live in accordance with the idea of human (good, welfare, reason) is questioned, and society is seen as a set of faceless units (singularity) without personal origin, so are neglected the questions about the ideal of man, the meaning and content of his life. It is concluded that the methodology of modern postmodernism is based on the idea of simulacra, which argues the course of a person’s life process in unconscious and undetermined existential motives, which do not pose the problem of morality. It is believed that a person has the right to always be different, even abnormal, not to obey any norms, rules and standards, not to question the essence and meaning of life, instead it is popularized a man-simulacrum as an indefinite unit, from the array of which arises a faceless broad community, not a human community with life-affirming, sincere and open relationships. It is argued that the substantiation of the fundamental principles of personality’s authentic morality primarily concerns its relationship with God, the Other, with himself, the community, the world, which is manifested in relation to various aspects of social life. At the same time, it was argued the existence of vertical and horizontal dimensions of morality  social nature and spiritual content. It is proved that the basis of spiritual morality is the law of effective (unconditional, absolute, equal to all) love for the Other, the liberation of the person from selfishness, the creation of freedom and universal personal responsibility. Instead, a person with social morality constantly has difficulties in realization of his moral attitude to the Other (dependence of attitude on the level of family ties, status closeness, individual characteristics) and problems with motivation for such behavior (non-consideration for the dignity of the Other, his needs for good, freedom, to be individuality). It is noted that in Ukrainian society today prevails morality of social nature and manifestations of personal immorality are common, so cleansing requires a sphere of moral attitude to others, based on the idea of man, the phenomenology of effective love, good and evil, life and death, conscience, justice, as well as respect for the right of the Other and the community to freedom and individuality. The scale of moral and immoral attitude to the Other is characterized, in which three levels are singled out - moral, morally neutral, immoral  and its eleven sublevels. The personal mechanisms and problem zones in realization of the person’s moral behavior are analyzed. The channels of its moral improvement in the covital contexts of culture, work, politics, everyday life are highlighted.